Robust 2DOF state-feedback PI-controller based on meta-heuristic optimization for automatic voltage regulation system - Gozde, Haluk (ISA transactions, 2020)
The Automatic Voltage Regulation (AVR) system which works within the synchronous generator[s] locally is defined as the closed loop control system that keeps the reactive power output at demanded value by adjusting exciter signal. Designing a proper control scheme for the AVR system to provide the desired level of voltage stability is an important research field. Nowadays, classic 1DOF PI-controller which takes into account only the load side disturbance is generally used in the AVR systems. In this study, to improve the robustness of this system towards the relatively severe disturbances caused from both load side and set point side, the 2DOF state feedback PI-controller which is tuned with a meta-heuristic optimization algorithm is proposed. Since only the error signal is minimized by using a simple cost function, this method can be applied simpler as independent to the system parameters, optimal coefficients are computed simpler. The superiority of the proposed controller is proved by applying stability, time-domain, frequency-domain and two different robustness analyses such as instantaneous and continuous disturbance analyses. It is observed from these analyses that the maximum overshoot and settling time obtained from the proposed control structure decrease more than a half. In addition, the immunity towards instantaneous and continuous disturbances significantly improve and the step responses in these cases stay in 2% band. At the end of the study, the implementation proposal related to the new control scheme is presented and interpreted in detail. •Firstly, the 2DOF PI-controller is designed for AVR system according to Vilanova et al. (2012).•To adjust the PI-parameters, well-known PSO is used, but it can be changed in the future works.•As main contribution, state feedback design is applied to the controller.•The comparative results obtained by using different investigations are presented.•Conclusively, the microcontroller-based implementation scheme is suggested.